Development and Initial Validation of the Activity Patterns Scale in Patients With Chronic Pain. - Esteve-Zarazaga, Rosa; Ramírez-Maestre, María del Carmen; Peters, Madelon L.; Serrano-Ibáñez, Elena Rocío; Ruiz-Párraga, Gema Teresa; López-Martínez, Alicia Eva (Elsevier, 2016)
Several self-report measures were used to identify 6 activity patterns in chronic pain patients: pain avoidance, activity avoidance, task-contingent persistence, excessive persistence, pain-contingent persistence, and pacing. Instruments for assessing pacing should include 3 pacing behaviors (breaking tasks into smaller tasks, taking frequent short rests, slowing down), each of which relate to a single goal (increasing activity levels, conserving energy for valued activities, and reducing pain). This article presents the Activity Patterns Scale (APS), which assesses these 6 activity patterns. Study 1 included 291 participants with chronic pain, and tested 3 structures using confirmatory factor analyses. The structure with the best fit had 8 factors corresponding to the hypothesized scales. High correlations in the expected direction were found between the APS subscales and the ‘‘Patterns of Activity Measure-Pain.’’ Study 2 included 111 patients with chronic pain, and aimed at examining the association between the APS subscales and adjustment to pain. It was found that that activity avoidance was associated with daily functioning and impairment. Negative affect was positively associated with activity avoidance and excessive persistence, and negatively associated with task-contingent persistence, which was also positively associated with positive affect. This study showed that the APS is a valid and reliable instrument for clinical practice and research
https://openpolicyfinder.jisc.ac.uk/id/publication/14183
Keywords: Dolor - Aspectos psicológicos; Dolor crónico; Ejercicio físico; Psicometría; Activity patterns; Avoidance; Persistence; Pacing; Chronic pain